2023
DOI: 10.1039/d2tb01867e
|View full text |Cite
|
Sign up to set email alerts
|

Poly(succinimide) nanoparticles as reservoirs for spontaneous and sustained synthesis of poly(aspartic acid) under physiological conditions: potential for vascular calcification therapy and oral drug delivery

Abstract: This paper describes the preparation of poly(succinimide) nanoparticles (PSI NPs) and investigates their properties and characteristics. Employing direct and inverse precipitation methods, stable PSI NPs with tunable size and narrow...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…PSI was synthesised using poly-condensation reactions of aspartic acid as described by Adelnia et al [34], Nakato et al [35] and Tomida et al [36]. Aspartic acid (21 g), H 3 PO 4 (1.5 ml) and sulfolane (75 ml) were separately poured into a 100 ml three-necked flask immersed in a 185 °C oil bath under nitrogen gas flow with 150 rpm over-head stirring.…”
Section: Synthesis Of Psimentioning
confidence: 99%
“…PSI was synthesised using poly-condensation reactions of aspartic acid as described by Adelnia et al [34], Nakato et al [35] and Tomida et al [36]. Aspartic acid (21 g), H 3 PO 4 (1.5 ml) and sulfolane (75 ml) were separately poured into a 100 ml three-necked flask immersed in a 185 °C oil bath under nitrogen gas flow with 150 rpm over-head stirring.…”
Section: Synthesis Of Psimentioning
confidence: 99%
“…This can be explained by the insolubility of PSI in water. When PSI is exposed to water, its structure collapses instantaneously, and polymer precipitation is evenly dispersed and blended in NaAlg before this mixture forms a hydrogel with CaCl 2 crosslinking, leading to a rough surface [31]. This demonstrates that PSI was incorporated into the hydrogel.…”
Section: Synthesis and Characterization Of Alg-psimentioning
confidence: 99%
“…PSI nanoparticles (NPs) were shown to hydrolyze slowly under physiological pH 7.4 conditions while being stable under acidic conditions. The ability of NPs to be dissolved under neutral conditions while maintaining stability in acidic environments is a highly desirable property for oral delivery technologies [31]. Therefore, it is considered that PSI exhibits potential for the development of medication delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that PASP could be spontaneously, inherently, and slowly synthesized in the physiological conditions from its precursor PSI. 25 In addition to its bioactivity, PSI, as a hydrophobic polymer, can also serve as a carrier of hydrophobic agents, providing a potential platform for the delivery of drugs that are clinically limited with drawbacks, such as low aqueous solubility and rapid metabolism/degradation. Due to the slow conversion to PASP, PSI NPs are expected to release their cargo in a sustained manner, consistent with their dissolution profile.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in our study we proposed using polysuccinimide (PSI), a precursor of PASP, instead of PASP to avoid potential side-effects associated with the direct administration of PASP. We recently showed that PASP could be spontaneously, inherently, and slowly synthesized in the physiological conditions from its precursor PSI …”
Section: Introductionmentioning
confidence: 99%